Malignant peripheral nerve sheath tumor of temporoparietal region of brain mimicking as glioma: A rare case report (Indian Journal of Case Reports, 2022)
Malignant peripheral nerve sheath tumor (MPNST) is exceedingly rare to occur intracerebrally. The incidence of this subtype is 0.001%. Their typical origin is from peripheral nerves of the limbs, trunk, and lumbar and brachial plexuses. It carries a poor prognosis despite aggressive management due to high chances of local recurrence. We present a case of MPNST occurring intracerebrally in a 60-year-old male patient. Imaging showed a 63 × 74 × 46 mm mass lesion in the left temporoparietal region with mass effect. The patient underwent left temporoparietal craniotomy with maximum gross dissection of the tumor. Histopathology was suggestive of spindle cell neoplasm. On immunohistochemistry, cells were positive for S-100 and SOX-10, which are consistent with the diagnosis of MPNST. The post-operative contrast-enhanced magnetic resonance imaging brain showed gross residual disease. Post-operative radiotherapy was given of intensity-modulated radiation therapy and chemotherapy of doxorubicin and ifosfamide.